Factors Associated With Participation and Change Over Time in Domestic Life, Peer Relations, and School for Adolescents With and Without Self-Reported Neurodevelopmental Disorders. A Follow-Up Prospective Study - Lygnegård, Frida; Augustine, Lilly; Granlund, Mats; Kåreholt, Ingemar; Huus, Karina (Frontiers in Education, 2018)
Even though participation in everyday events is a vital part in the fulfilment of human rights, adolescents with neurodevelopmental disorders often face participation restrictions in every-day activities. Few studies have investigated the predictors for participation in different contexts, over time and in relation to the same outcome variables. The objective of the current study was therefore to investigate predictors of change in participation operationalized as frequency of attendance and perceived importance in domestic life activities, peer related activities, and school activities as experienced by adolescents with and without self-reported neurodevelopmental disorders. Method: Associations with participation, both in terms of frequency and perceived importance, in domestic life, peer relations, and the school setting were investigated using six independent variables measuring experience of time and self, sex, age, stress, support from siblings, and atmosphere in family at two-time (with approximately 2 years in between). The sample consisted of adolescents with and without self-reported neurodevelopmental disorders (n= 916). Adolescents with self-reported neurodevelopmental disorders were n=154 and adolescents without self-reported neurodevelopmental disorders was n= 762. Data was collected via self-reported questionnaires administered in schools. Results: Three key findings are presented. 1) more factors were associated with participation outcomes at time1 for adolescents without NDD than for adolescents with NDD, but this difference in the number of factors decreases with time; 2) few associations were related to time for both adolescents with and without NDD; and 3) patterns of predicting variables were different for adolescents with and without NDD. Conclusion: The findings indicate that the factors related to participation in and outside school differs between groups, when the impairment or disability is not considered as a predictor for participation. This study supports the need for using a multidimensional developmental and contextual perspective in addressing enhanced participation for adolescents with neurodevelopmental disorders.